A connected history of audiovisual translation Elements for consideration - Yves Gambier; Haina Jin (JOHN BENJAMINS PUBLISHING CO, 2022)
Why do we need a history of audiovisual translation? The elements of such a history cannot be tackled without any context, especially outside of a history of cinema, understood both as an art made of techniques and a business. And what kind of history do we need? We try here to define the conditions and resources for a connected and comparative history and deal with a few methodological challenges.